The importance of measuring the delivery of services via commercial presence of offshore foreign affiliates: Some case studies from Australian business experience - Jane Drake-Brockman (Asian Development Bank Institute (ADBI), 2011)
There are major difficulties associated with measurement of each of the four modes of services trade delivery as defined in the General Agreement on Trade in Services (GATS): cross-border supply, consumption abroad, commercial presence, and movement of natural persons. The consequence is that the extent of global trade in services is hugely underestimated and the services sector does not receive the trade and economic policy attention it deserves. The global economy meanwhile misses out on the productivity gains that focused reform of services sectors could generate. Australia is one of the world's most services-intensive economies. Of the 20 largest world economies, Australia's is fourth only to the United States, United Kingdom, and France in services. This means Australias future economic growth will be substantially determined by improvements in productivity and competitiveness in services. Just a small rise of 0.1% in services sector productivity would result in a sustained annual rise of over A1 billion in Australia's gross domestic product. But the services sector does not receive the policy focus these economic fundamentals would justify. This is largely because the balance of payments data measures Australia's services exports at less than 25% of total exports, consistent with World Trade Organization estimates that services account for roughly 20% of world trade. In Australia's case, sufficient business survey work has been done to leave no remaining doubt that the balance of payments data have needed to be both improved in their own right as well as supplemented with foreign affiliates' trade in services (FATS) data to shed greater light on the services sector's share in international business. This paper highlights recent business case studies in Australia, which demonstrates the importance of intensifying official efforts to enhance collections of services export data and to measure specifically Mode 3 (Commercial Presence) delivery of international services. The studies are drawn chiefly from legal services and financial services but also cover the information and communication technology and architecture/building design sectors. This paper focuses on some of the problems commonly experienced in relation to statistics regarding international trade in services. It deals moreover only with case studies drawn from Australian business experience; and refers to practices and collections of the Australian Bureau of Statistics (ABS).
Keywords: F14; F23; M16; M21; 330; Internationaler Dienstleistungsverkehr; Offshoring; Auslandsniederlassung; Australien